Kv1.3 Channel as a Key Therapeutic Target for Neuroinflammatory Diseases: State of the Art and Beyond - Wang, Xiaoli; Li, Guoyi; Guo, Jingkang; Zhang, Zhiping; Zhang, Shuzhang; Zhu, Yudan; Cheng, Jiwei; Yu, Lu; Ji, Yonghua; Tao, Jie (Frontiers in Neuroscience, 2020)
It remains a challenge for the effective treatment of neuroinflammatory disease, including multiple sclerosis, stroke, epilepsy, Alzheimer's and Parkinson's disease. The voltage-gated potassium Kv1.3 channel is of interest, which is considered as a novel therapeutic target for treating neuroinflammatory disorders due to its crucial role in subsets of T lymphocytes as well as microglial cells. The ShK toxin from the sea anemone Stichodactyla helianthus is proved as a potent blocker of Kv1.3. One of the synthetic analogs ShK-186, being developed as a therapeutic for autoimmune diseases, has successfully completed first-in-man Phase 1 trials. In addition to addressing the recent progress on the studies underlying the pharmacological characterizations of ShK on multiple sclerosis, the review will also explore the possibility for clinical treatment of the peptide on other neuroinflammatory diseases.